2021
DOI: 10.1055/a-1406-0356
|View full text |Cite
|
Sign up to set email alerts
|

Der Einfluss von Profession und Erfahrung hinsichtlich der kriteriengeleiteten Beurteilung der Schuldfähigkeit bei paraphilen Störungen – eine randomisierte kontrollierte Studie

Abstract: Zusammenfassung Ziel der Studie Die Studie untersucht, ob Beruf und Erfahrungsgrad einen Einfluss auf die kriteriengeleitete Beurteilung der Schuldfähigkeit bei paraphilen Störungen haben. Methodik Zwei verschiedene Kriterienkataloge wurden von 3 verschiedenen Berufsgruppen (Psychologen, Psychiater und Juristen), jeweils mit einem unterschiedlichen Ausmaß an Vorerfahrung, hinsichtlich ihrer prädiktiven Validität überprüft. Hierzu bewerteten 349 Rater die Kriterien eines von 2 Kriterienkatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…We found women participants (for frotteuristic disorder) and participants who endorsed the view that any atypical pattern of sexual interest should be considered abnormal (for exhibitionistic disorder) were more likely to endorse requiring treatment as a part of criminal sentencing. Dobbrunz et al (2021) also found an effect of gender of the assessor in the evaluation of paraphilic disorders.…”
Section: Discussionmentioning
confidence: 83%
“…We found women participants (for frotteuristic disorder) and participants who endorsed the view that any atypical pattern of sexual interest should be considered abnormal (for exhibitionistic disorder) were more likely to endorse requiring treatment as a part of criminal sentencing. Dobbrunz et al (2021) also found an effect of gender of the assessor in the evaluation of paraphilic disorders.…”
Section: Discussionmentioning
confidence: 83%